Analisis perhitungan dan pelaporan Pajak Penghasilan pasal 25 berdasarkan UU Nomor 7 Tahun 2021 di Laboratorium Klinik Kanaka - Tumbelaka, Dean Enriqe; Sondakh, Jullie J.; Rondonuwu, Sintje (Manajemen Bisnis dan Keuangan Korporat, 2025)
This study evaluates the compliance of Income Tax Article 25 (PPh Pasal 25) calculation and reporting at Kanaka Clinical Laboratory with the provisions of Law No. 7 of 2021 on the Harmonization of Tax Regulations. Using a qualitative descriptive approach, data were collected through interviews and document analysis of the company’s 2023 tax records. The findings reveal a significant discrepancy between the calculated Income Tax payable under the reduced rate of 11% (IDR 154,964,150) and the amount reported in the Annual Tax Return (IDR 195,709,635), resulting in an overpayment of IDR 40,745,485. This discrepancy indicates potential misapplication of tax rates or classification errors. Nevertheless, the study finds that the administrative process of reporting—including installment payments, filing deadlines, and submission procedures—complies with the legal requirements of Law No. 7 of 2021. These results highlight the importance of accurate tax calculation and internal controls to ensure compliance and minimize financial risk for corporate taxpayers.